Early Microbe Contact and Obesity Risk: Evidence Of Causality?. (July 2016) - Isolauri, Erika; Salminen, Seppo; Rautava, Samuli
Abstract : ABSTRACT: The industrialized societies worldwide are in the middle of epidemics of diet-related chronic diseases, obesity being the common denominator. Lately, these conditions have been linked with a distinct microbiota composition in affected individuals different from that of healthy individuals. In particular, dysbiosis during critical stages of development induces lasting alterations in the immune and metabolic phenotype. The compositional development of the gut microbiota, again, is highly sensitive to environmental influences such as maternal health and nutrition, the mode of delivery, early feeding and antibiotic use. Shifts in the microbiota by high-energy diet increase energy extraction and storage, provoke a low-grade inflammatory response and impair gut barrier function, and, consequently, result in obesity and metabolic disease. A lower abundance of butyrate-producing bacteria and lower overall richness of bacteria has been associated with increased metabolic disease risk in humans. Recent reports suggest that Akkermansia type bacteria or butyrate producing microbes may have anti-inflammatory potential and enhance intestinal barrier function, which may both alleviate obesity and related metabolic complications. Thus we are not directly what we eat or our mother eats, but what our microbiota eat and how the collective composition of the microbiome is modified by the diet. On this basis, altering the intestinal microecosystem may be taken as a key target to attain prophylactic or therapeutic effects in metabolic and inflammatory conditions. Tools for such modulation include specific probiotic bacteria and potentially also non-digestible carbohydrate components able to modify microbiota composition and activity.